ANALISIS PUTUSAN HAKIM TENTANG PEMBEBANAN NAFKAH DALAM PERKARA CERAI GUGAT : (Studi Pada Putusan Perkara Nomor: 1128/Pdt.G/2021/Pa.Bgr) - Khoerunnisa, Ananda; Arif, Suyud; Gustiawati Mukri, Syarifah (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2022)
Marriage is a strong contract or mitsaqan ghalizhan to obey Allah's commands with the aim of realizing a harmonious and loving household (sakinah, mawaddah wa rahmah). If the purpose of marriage is not achieved, then divorce is an act to break the marital relationship. The burden of living is part of the consequences of divorce which often causes irregularities when it occurs in divorce cases. In the decision on the divorce case number 1128/Pdt.G/2021/Pa.Bgr, the judge charged a living that was not in accordance with article 149 of the Compilation of Islamic Law. Therefore, this study was conducted to analyze the legal basis and considerations of the Bogor Religious Court Judges in deciding the burden of living and determining the amount. This research is qualitative research using normative-empirical legal research methods, through a case study approach. Based on the results of the study, the legal basis for the Panel of Judges in deciding the burden of past expenses refers to Article 80 of the Compilation of Islamic Law paragraph 4, regarding iddah and mut'ah living refers to the Indonesian Ministerial Regulation Number 3 of 2017 concerning guidelines for adjudicating women's cases in conflict with the law and the results of the meeting formulation. The Chamber of Religion as outlined in the Circular Letter of the Supreme Court of the Republic of Indonesia Number 3 of 2018 A. Regarding child support, it refers to Article 105 letter c of the Compilation of Islamic Law. Meanwhile, in determining the number of expenses for living expenses, the Judge considers two things, namely the husband's income and the needs of each party which are adjusted to the ability, fairness, and justice as well as the ability of the Defendant.